Semi-transparent silver electrodes for flexible electronic devices prepared by nanoimprint lithography - Schumm, Benjamin; Wisser, Florian M.; Mondin, Giovanni; Hippauf, Felix; Fritsch, Julia; Grothe, Julia; Kaskel, Stefan (Journal of Materials Chemistry C, 2013)
The preparation of mechanically flexible and optically transparent electronic circuits plays a key role in the development of next-generation display technologies. Silver nano-gratings are of particular interest due to their excellent conductivity and adjustable transmittance. Printed on polymeric substrates they are suitable for an application in flexible opto-electronic devices. Here, we present the preparation of a smart silver precursor system combining both the ability of cheap and scalable nanoimprint patterning and simple thermal silver reduction. Homogeneous silver line and grid patterns with line widths down to 400 nm are prepared using poly(dimethylsiloxane) stamps in a thermal nanoimprint lithography process. Relatively low process temperatures allow the film formation on polymeric substrates. Semi-transparent silver electrodes with a resistance of 2.8 ohm are patterned on polyimide foils to prepare flexible electro-luminescence devices. A detailed investigation of the precursor's thermal decomposition behaviour as well as the resulting electrical and optical properties of the films is offered. © 2013 The Royal Society of Chemistry.
CRIS-Team Scopus Importer:2023-03-20